An approach to evaluate the effect of inflammatory microvesicles on Ca2+ handling in human-induced pluripotent stem cell-derived cardiomyocytes - Fischer, Dania; Sha’sha’a, Mishkaat; Schenz, Judith; Tayan, Aycan; Mertens, Christina; Decker, Sebastian; Gallenstein, Nadia; Dietrich, Maximilian; Lajqi, Trim; Hafner, Anna; Weigand, Markus A.; Ullrich, Nina D. (Experimental biology and medicine, 2025)
Microvesicles (MV) isolated from septic individuals were observed to impact systemic hemodynamics and cardiac function. The aim of this in vitro study was to analyze the effects of TNFα-induced endothelial MV (TMV) and MV from septic patients (SMV) on beating frequency and Ca2+ transient kinetics of human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM). MV were isolated from supernatants of TNFα-stimulated primary human pulmonary microvascular endothelial cells (HPMEC) and plasma from 20 sepsis patients by ultracentrifugation and quantified using flow cytometry. Spontaneous Ca2+ transients were measured in hiPSC-CM using the Ca2+-sensitive ratiometric indicator fura-2 at different time points of incubation with different MV concentrations. At 16 h of incubation, higher MV concentrations showed significant differences, especially regarding decay and beating frequency. Despite high variability, at 10 × 106 MV/mL and 16 h of incubation, TMV significantly decreased frequency compared to control MV (CMV). SMV from septic patients did not reveal any significant effects on Ca2+ transients under these experimental settings. MV isolated from control or TNFα-treated HPMEC affected Ca2+ handling and spontaneous activity of hiPSC-CM, however, the measured effects were not consistent throughout the different conditions. Further refinement of the experiment conditions is needed to specify the exact conditions for crosstalk between endothelium-derived MV and cardiomyocytes.